Psychological Burn- out among teachers working at faculties of education and colleges in the Southern region Saudi Arabia and its relationship to some demographic variables - Al- Awad, Mona Abdullatif; Al- Sayed, Sahar Abdulrahim Awad (Journal of Educational and Psychological Sciences, 2019)
This research goal to Identify the psychological Burn- out among teachers working at faculties of education and colleges in the Southern region Saudi Arabia and its relationship to some demographic variables. The researcher used descriptive total sample. The sample consisted of (238)teachers selected by using stratified random sampling method. The research tools comprised primary information form and the psychological Burn- Out scale designed by Kristina Maslash and Susan Jackson (1979). The researcher used statistical package for Social Sciences (spss).The search has reached the following conclusions:1- the Burnout among teachers working in colleges of education and setting parameters، South Saudi Arabia to rise.2- There is a direct correlation function between burnout and the lifetime of teachers workers education parameters setting parameters in southern Saudi Arabia.3- There is a direct correlation function between burnout and years of experience of working parameters of the colleges of education and setting parameters in southern Saudi Arabia.4- no statistical function relationship between burnout and qualification for teachers employed in colleges of education and setting parameters in southern Saudi Arabia.5- There are no statistical differences in Burnout depending on the social situation of working parameters of the colleges of education and setting parameters employed in colleges of education and setting parameters in southern Saudi Arabia.6- There are no statistically significant differences in Burnout depending on the nationality of the working parameters of the colleges of education and setting parameters in southern Saudi Arabia.
Keywords: psychological burnout; colleges of education; Saudi Arabia; lectures